2020
DOI: 10.1097/ijg.0000000000001605
|View full text |Cite
|
Sign up to set email alerts
|

Visual Field Artifacts From Face Mask Use

Abstract: Purpose: The coronavirus (COVID-19) pandemic has had a profound impact on how glaucoma care is delivered, necessitating reduced clinic flow, social distancing, and use of face coverings by patients and staff. This case highlights the need to be aware of improperly fitted face masks as a cause of artifact on standard automated perimetry (SAP). Clinical Presentation: A 32-year-old female underwent SAP with the 24-2 SITA Fast test of the Humphrey Field Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 3 publications
1
31
0
2
Order By: Relevance
“…To the best of our knowledge, the data of the present study are the first ones investigating an impairment of visual field due to mouth-nose-masks in healthy eyes. Only two recent case reports had previously shown visual field artefacts from using a mouth-nose-mask in clinical visual field testing due to fogging of the trial lens [ 16 , 17 ]. The mask can be taped to the nose [ 16 ] or can be tied around the head with a special technique, in which the superior and inferior ties cross before the ear in order to reduce fogging [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, the data of the present study are the first ones investigating an impairment of visual field due to mouth-nose-masks in healthy eyes. Only two recent case reports had previously shown visual field artefacts from using a mouth-nose-mask in clinical visual field testing due to fogging of the trial lens [ 16 , 17 ]. The mask can be taped to the nose [ 16 ] or can be tied around the head with a special technique, in which the superior and inferior ties cross before the ear in order to reduce fogging [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, people have been wearing many different kinds of masks, sometimes home-made or ill-fitting. Two case reports have already reported about visual field artefacts from using a mouth-nose-mask in clinical visual field testing by fogging of the trial lens or incorrect wearing of the mask [ 16 , 17 ]. Considering different sizes and shapes of the mouth-nose-masks, there might be different effects of visual field restriction.…”
Section: Introductionmentioning
confidence: 99%
“…In pattern A, the median number of new locations with a sensitivity lower than 95% considered normal was 14 (6-26), with a median sensitivity of −4.94 dB (−12.86 to −2.33). In pattern B, the median number was 6.5 (3)(4)(5)(6)(7)(8)(9)(10)(11), with a median sensitivity of −5.38 (−9.14 to −3.83). The median number of locations already affected in the pre-COVID test whose sensibility impaired in VF test 1 was 4 (0-17) in pattern A and 9 (2-20 in pattern B).…”
Section: Figurementioning
confidence: 99%
“…A recent report has shown that wearing a face mask while performing a VF test may cause inferior artefacts due to the fog on the trial lens. 4 Furthermore, face masks seem to be a distracting factor to make a reliable test, as patients refer to feeling uncomfortable and short of breath.…”
Section: Introductionmentioning
confidence: 99%
“…Face masks represent a new cause of visual field artifacts that may mimic pathologic field defects: indeed, they block the vision of one's lower far peripheral visual field, which is crucial for visuomotor feedback when engaged in walking. And the fact that one is visually handicapped when wearing a face mask is almost never consciously realized [46], when it is a major public health problem [47] because: 1. Falls are the second leading cause of accidental or unintentional injury deaths worldwide, 2.…”
Section: Psychomotor Effectsmentioning
confidence: 99%